2011
DOI: 10.1007/s11517-011-0808-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of upper-limb motor control in robot-aided rehabilitation

Abstract: This paper is focused on the multimodal analysis of patient performance, carried out by means of robotic technology and wearable sensors, and aims at providing quantitative measure of biomechanical and motion planning features of arm motor control following rehabilitation. Upper-limb robotic therapy was administered to 24 community-dwelling persons with chronic stroke. Performance indices on patient motor performance were computed from data recorded with the InMotion2 robotic machine and a magneto-inertial sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 50 publications
1
88
0
3
Order By: Relevance
“…2a and 2b). In a previous review on metrics from the use of robotic systems, Zoilo et al noted that the information provided by each of these measures may not be exclusive, and the names used in their survey may differ from those used in the original and cited papers (Zoilo et al, 2011). In the present review, we highlighted the same difficulty.…”
Section: Upper Extremity Movement-related Metricsmentioning
confidence: 68%
See 2 more Smart Citations
“…2a and 2b). In a previous review on metrics from the use of robotic systems, Zoilo et al noted that the information provided by each of these measures may not be exclusive, and the names used in their survey may differ from those used in the original and cited papers (Zoilo et al, 2011). In the present review, we highlighted the same difficulty.…”
Section: Upper Extremity Movement-related Metricsmentioning
confidence: 68%
“…In the study performed by Zoilo, metrics were classified into two groups according to metrics related to biomechanical characteristics and metrics related to movement aspects (Zoilo et al, 2011). Within the review that we present, metrics found in literature analyze different movement characteristics or quality measures, which have been shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviews address some relevant topics related with the rehabilitation robotics research field: overview of upper-limb rehabilitation devices, different approaches to neurorobotic and hybrid management of lower limb motor disorders and a review about the assessment of the effectiveness of robot-facilitated neurorehabilitation for relearning motor skills. Moreover, the original papers cover a wide range of relevant topics like: virtual rehabilitation, rehabilitation robotic devices to train activities of daily living, electrical stimulation, assessment of upper-limb motor control in robotaided rehabilitation, new assistance algorithms based on adaptative oscillators, upper-limb rehabilitation devices based on pneumatic technology, bilateral robot-mediated therapy and assistive robotic devices for elderly people and for children with special needs.Classical devices for upper-limb rehabilitation clinical research, like ARMin [8], and many others are revised on Rui Loureiro et al [15]. Tables in this work give a present update of the well-known devices.…”
mentioning
confidence: 99%
“…Classical devices for upper-limb rehabilitation clinical research, like ARMin [8], and many others are revised on Rui Loureiro et al [15]. Tables in this work give a present update of the well-known devices.…”
mentioning
confidence: 99%